Design and fabrication of shoes rack - Amin Khairi, Rosli (2009)
This report presents the design and fabrication shoes rack for use in Masjid UMP. This design and fabrication of shoes rack according to the type of the place that we want to place it. Shoes rack is always used in many type of place such as school, office, Masjid, house and etc. The idea of the fabricating of this shoes rack is based on student’s creativity and own inspiration. The selection of suitable materials in the fabricating of this shoes rack is a loaded material which has lightweight, long life-span and can detain heavy load. Materials are proposed for the fabrication of the shoes rack is a mild steel carbon material. In this report, we’ll also be having more to the fabrication and analysis of this shoes rack.